Astrocytic Ca2+ signaling mediated by the endoplasmic reticulum in health and disease - Yohei Okubo (Journal of Pharmacological Sciences, 2020)
Astrocytes generate robust intracellular Ca2+ signals that are assumed to be key regulators of astrocytic function. Among various Ca2+ mobilization mechanisms, Ca2+ release from the endoplasmic reticulum (ER) via the inositol 1,4,5-trisphosphate receptor (IP3R) has attracted attention as a major component of astrocytic Ca2+ signaling. Manipulation of astrocytic IP3–Ca2+ signaling, such as genetic deletion of the type 2 IP3R, has revealed multifaceted roles of astrocytic ER Ca2+ release in health and disease. Recent developments in Ca2+ imaging techniques including ER intraluminal Ca2+ imaging have been indispensable in determining the physiological and pathophysiological significance of astrocytic ER Ca2+ release via IP3Rs. Beneficial and detrimental roles of IP3R-dependent Ca2+ release in astrocytes have been revealed in wide variety of disorders in the brain, strongly suggesting astrocytic IP3–Ca2+ signaling as a novel and promising therapeutic target.